Comparison of central corneal thickness and intraocular pressure measured with two different tono/pachymeter devices in non-glaucomatouse children. Issue 6 (November 2021) - Teberik, Kuddusi; Eski, Mehmet Tahir; Ankarali, Handan
Purpose: The goal of this research is to compare the intraocular pressure (IOP) and the mean central corneal thickness (CCT) values obtained from the measurements with Nidek NT-530P and Canon TX-20P devices with the values obtained by ultrasound pachymetry (UP) and Goldmann applanation tonometry (GAT) in children. Methods: This prospective study was conducted with 119 healthy children. The measurements were repeated three times for each eye. The intraclass correlation coefficient (ICC) was used to assess the correlation between the measurements obtained from different devices. The Bland–Altman plot was used to analyze the agreement between two different devices graphically. The measurements were taken in the same order in all subjects: TX-20P, NT-530P, UP, and GAT. Results: The mean age of the children was 10.1 ± 3.2 (6–17) years. The mean CCT values for the eyes were 568.90 and 569.68 (TX-20P), 571.44 and 566.37 (NT-530P), 564.77 and 564.67 μm UP, (right and left, respectively). The highest correspondence observed for CCT was between UP and NT-530P devices (ICC, 0.982, the left eye). The mean IOP measurements for Canon TX-20P, NT-530P, and GAT were 16.5 ± 3.2, 16.3 ± 3.2, and 16.8 ± 3.6 mmHg for the right eyes, respectively, while those for the left eyes were 16.6 ± 3.1, 16.2 ± 3.3, and 16.8 ± 3.7 mmHg. The highest correspondence was noted between measurements obtained using GAT and Nidek NT-530P devices (ICC, 0.945, in the left eye). Conclusion: Tono/pachymetry devices in the healthy children are provides significant agreements with the gold standard methods for IOP and CCT measurements. Clinical Trial Registration number: 2016-94